2021
DOI: 10.3390/horticulturae7080255
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Handheld Bluetooth Colourimeter and Its Application to Measuring the Effects of Time from Harvest, Row Orientation and Training System on Nectarine Skin Colour

Abstract: This work aimed to (i) determine the reliability of a portable Bluetooth colourimeter for fruit colour measurements; (ii) characterise the changes in quantitative skin colour attributes in a nectarine cultivar in response to time from harvest; and (iii) determine the influence of row orientation and training system on nectarine skin colour. The skin colour attributes measured with the colourimeter, namely L*, a* and b*, were calibrated and validated against a reference spectrophotometer. C* and h° were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…McGuire (1992) highlighted how the use of CIELab and/or LCh color attributes guarantees an objective color measure. Literature showed that h is associated with redness and maturity in peach and nectarine (Ferrer et al 2005;Robertson et al 1990;Scalisi et al 2020Scalisi et al , 2021a. Our results showed good accuracy of h predictions in peach and nectarine (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…McGuire (1992) highlighted how the use of CIELab and/or LCh color attributes guarantees an objective color measure. Literature showed that h is associated with redness and maturity in peach and nectarine (Ferrer et al 2005;Robertson et al 1990;Scalisi et al 2020Scalisi et al , 2021a. Our results showed good accuracy of h predictions in peach and nectarine (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…1C). The colorimeter generated different color attributes in the CIELab/LCh color wheel (i.e., L*, a*, b*, C*, and h ), as previously shown by Scalisi et al (2021a). Color was predicted with the mobile platform within the same bounding boxes used for fruit number and diameter predictions.…”
Section: Estimations Of Crop Parametersmentioning
confidence: 99%
“…The a* value corresponds to the degree of red or green color; the -a* value is green, and the a* value is red. Specifically, a* and hue angle are two good indicators of fruit maturity in peach [41], nectarine [42], and most fruits that turn from green to red. CIELab color parameters can be derived from RGB by image processing.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The use of colourimeters that measure colour in different colour spaces (e.g., RGB, CMYK, XYZ CIELab/LCh) can be found in the relevant literature, but they often required contact devices such as portable spectrometers [2]. For example, a* and hue angle were successfully linked to maturity in peach and nectarine [3][4][5][6][7], and hue angle was related to harvest time in 'Majestic Pearl' nectarines in a recent study [8]. These devices have proved reliable and useful for objectively measuring skin colour in different crops.…”
Section: Introductionmentioning
confidence: 99%
“…Although Cartographer has been validated and used for measurements of fruit number, fruit colour and size in peach and nectarine cultivars [13], the consistency of fruit colour measurements in different light environments or time of the day, and the relationship between fruit colour and ripeness or harvest time need to be investigated to determine if scanning the orchards can provide a valuable tool to plan harvest time based on objective fruit colour thresholds. This work aimed to (i) derive a fruit skin colour development index (CDI, ranging from 0 to 1) that can be easily calculated from hue angle data-a CIELab colour attribute that was successfully related to harvest time and maturity in stone fruit [3][4][5][6][7][8] using a fast-scanning mobile platform; (ii) determine the temporal variability of CDI readings when measurements are collected at different times of the day thereby providing changing light environments on different sides of the canopy; and (iii) test the relationship between the CDI and a conventional fruit maturity index used in peach and nectarine. One of our propositions was that collecting big data on the entire fruit population in an orchard block would offset the need to separate background and foreground skin colour for maturity estimation; thus, our premise is that the overall colour estimated on large samples of fruit in the orchard can support harvest decision making.…”
Section: Introductionmentioning
confidence: 99%